Wire breakage and deflection caused by nozzle jet flushing in wire EDM. Issue 1 (2015) - Okada, A.; Konishi, T.; Okamoto, Y.; Kurihara, H.
Abstract High flow rate in nozzle jet flushing is effective for smooth debris exclusion from the wire EDM gap, but this leads to large wire deflection and vibration, resulting in the wire breakage and low shape accuracy. In this paper, the influence of nozzle jet flushing on wire breakage was experimentally investigated with varying the machined kerf length and machining conditions. Furthermore, the flow fields and debris residence time in the kerf, hydrodynamic stress distributions acting on the wire, and wire deflections were numerically analyzed. Based on the analyzed results, the causes of wire breakage were discussed.